The Values of Character Education in Sufism (A Case Study on Tarekat Naqsabandiyah-Khalidiyah Followers in Banyumas, Central Java, Indonesia) - Munjin Munjin (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
In now days, character is to be something very important in a technological era. If the materialistic advantages and benefits obtained from the advancement of the industrial era are not followed by the adequacy of immaterial factors, it will certainly bring about chaos in personal and social lives. Furthermore, the impact of the two sides disharmony will at least trigger three things. First, moral decline in community, second, the decreasing sense of togetherness and unity, third, interpersonal interaction has changed. So, human being needs identity and character in order to not experience disorientation in life. This paper aims to describe the characteristics of the disciples of Tarekat Naqsabandiyah-Kholidiyah in central Java, Indonesia and to analyze how the values of character education formed within the disciples of Tarekat Naqsabandiyah Khalidiyah. The methods used in collecting data were in depth interview, observation, and documentation. Having collected, they would be analyzed by steps like collecting, reduction, displaying data and drawing conclusion. The result showed internalization of the values were performed by integrated ways which combined either internal or external factors. Internal factors was started by pure motivation in each disciples’ inner heart. The external factor consisted of family, tarekat teaching, mursyid model, and jama’ah. The educational character along with the jama’ah tarekat can be categorized into three major characters namely; wisdom, keep avoiding the bad deed, and courage. These characters are also contained in educational character, and the most important thing is how the formal education can imitate the method used in building that character